Peanut seed cultivars with contrasting resistance to Aspergillus parasiticus colonization display differential temporal response of protease inhibitors - Muller, Virginia (2017)
Significant efforts are being made to minimize aflatoxin contamination in peanut seeds and one possible strategy is to understand and exploit the mechanisms of plant defense against fungal infection. In this study we have identified and characterized, at biochemical and molecular levels, plant protease inhibitors (PPIs) produced in peanut seeds of the resistant PI 337394 and the susceptible Forman cultivar during Aspergillus parasiticus colonization. With chromatographic methods and 2D-electrophoresis-mass spectrometry we have isolated and identified four variants of Bowman-Birk trypsin inhibitor (BBTI) and a novel Kunitz-type protease inhibitor (KPI) produced in response to A. parasiticus colonization. KPI was detected only in the resistant cultivar, while BBTI was produced in the resistant cultivar in a higher concentration than susceptible cultivar and with different isoforms. The kinetic expression of KPI and BBTI genes along with trypsin inhibitory activity was analyzed in both cultivars during infection. In the susceptible cultivar an early PPI activity response was associated with BBTI occurrence. Meanwhile, in the resistant cultivar a later response with a larger increase in PPI activity was associated with BBTI and KPI occurrence. The biological significance of PPI in seed defense against fungal infection was analyzed and linked to inhibitory properties on enzymes released by the fungus during infection, and to the antifungal effect of KPI.